PENENTUAN PENYUSUTAN ASET TETAP PADA MANAJEMEN ASET MENGGUNAKAN ALGORITMA BINARY SEARCH - Fitri Anggraeni; Dewi Sahara Nasution; Satria Putra Utama; cahyadi; Dwi Purnomo (Universitas Majalengka, 2024)
Assets are objects that have value and must be recorded, also commonly referred to as wealth. Assets can be capital, objects, land and buildings. The increasing number of assets will continue to grow and get bigger, problems arise when maintaining and monitoring the value of assets that have dynamic value over time. This research aims to group asset data using the Binary Search algorithm. So it will be easy to identify and know the final asset value which will be used by company or organizational decision makers in terms of asset renewal or asset replacement.